2015
DOI: 10.1002/lno.10071
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and spatial distribution of autotrophic communities within and between ice‐covered Antarctic lakes (McMurdo Dry Valleys)

Abstract: We compared the spatial distribution and diversity of autotrophic microbial communities among four permanently ice-covered, chemically stratified lakes located in the Taylor (Lakes Bonney-east and west lobes, Fryxell), and Wright (Lake Vanda) Valleys of the McMurdo Dry Valleys (Victoria Land, Antarctica). Clone libraries were constructed for major carbon fixation genes (rbcL isoforms IA/B and ID; cbbM; nifJ). Real time quantitative polymerase chain reaction assays were also developed for each of these markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 75 publications
9
62
0
Order By: Relevance
“…1, P4). The 18S rRNA sequences from these SAGs were very similar to sequences recovered from clone libraries generated from 13-m-deep waters from the east and west lobes of Lake Bonney (29), and recent reports suggested that haptophyte communities related to this organism are key primary producers in this lake (28,30,55). Communities of Isochrysis dominate the chemoclines of the east and west lobes of Lake Bonney (28).…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…1, P4). The 18S rRNA sequences from these SAGs were very similar to sequences recovered from clone libraries generated from 13-m-deep waters from the east and west lobes of Lake Bonney (29), and recent reports suggested that haptophyte communities related to this organism are key primary producers in this lake (28,30,55). Communities of Isochrysis dominate the chemoclines of the east and west lobes of Lake Bonney (28).…”
Section: Resultssupporting
confidence: 60%
“…The 18S rRNA sequences from these SAGs were very similar to sequences recovered from clone libraries generated from 13-m-deep waters from the east and west lobes of Lake Bonney (29), and recent reports suggested that haptophyte communities related to this organism are key primary producers in this lake (28,30,55). Communities of Isochrysis dominate the chemoclines of the east and west lobes of Lake Bonney (28). Several recent studies using quantitative PCR analyses to monitor the abundance of photosynthetic functional genes (rbcL and psbA) indicated that, in contrast to chlorophyte populations, the abundance (DNA) and activity (RNA) of haptophyte populations are not correlated with light availability (28,55).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…In traversing the oxycline, we expect a change in microbial community, both functionally and compositionally, as described for planktonic communities (25). Furthermore, it is not known how the composition and dominant metabolisms of bacteria other than cyanobacteria shift with lake depth or redox gradients and how these changes might relate to observed shifts in macroscopic mat morphology with lake depth (18).…”
Section: T He Mcmurdo Dry Valleys (Mdv) Region Of Southern Victoriamentioning
confidence: 99%